Jason D. answered • 10/11/16

Tutor

4
(1)
Tutoring Math and Science for All Ages

So let us name each mouse. Mouse 1 will weigh a and mouse 2 will weigh b

So, our equation is

a + b = 66

_{grams}now, mouse b weighs a + 0.2a so we can replace b with a + 0.2a. plug that into the original equation.

a + (a + .2a) = 66

_{grams}we can combine these terms to get

2.2a = 66

_{grams}solve for a you get mouse 1 weight

a = 66/2.2 = 30 grams

mouse 1 weighs 30 grams

now, we can replace the equation we used for b to get mouse two's weight

b = a + 0.2a = 30 + 0.2(30) = 36 grams

mouse 2 weighs 36 grams

to verify plug these back into the first equation we made

a + b = 66

30 + 36 = 66 grams